Enkulturasi dan Akulturasi Budaya Menurut Paulus - Hagai Kuncoro; Robinson Rimun; Budiyono Budiyono (Jurnal Teologi Kontekstual Indonesia, 2022)
Service in a cultural context is needed. God set an example by entering into the context of human culture through Jesus Christ. The disciples and the Apostle Paul also preached the Gospel by adjusting themselves to the enculturation and acculturation of the local culture. This study aims to examine the attitude of the apostle Paul's enculturation and acculturation. The method used is qualitative with hermeneutic and literature studies. The research found that Paul applied God's wisdom in his outreach based on the awareness of love and awareness as a messenger of the gospel. He mingled with lowly people, felt what they felt, followed their way of life and general rules without having to taint the principles of truth that had been engraved in him. In a sense, even though Paul lived in a mingling with them, Paul did not compromise on sin. This is done so that evangelism can be done effectively.